Two new earthworm species (Annelida, Oligochaeta, Megascolecidae) from the Mekong delta, Vietnam - Nguyen, Tung T.; Lam, Dang H.; Nguyen, Anh D. (Zootaxa, 2022)
Two new earthworm species are described from the Mekong Delta, Southern Vietnam (An Giang and Ben Tre Provinces), namely Amynthas reductus sp. nov. and Metaphire giengensis sp. nov. The former is recognized by having a pair of spermathecal pores in 6/7, numerous genital markings in transverse lines in 17/18, and spermatheca with strongly reduced diverticula. The latter is distinguished by having two pairs of spermathecal pores in 5/6/7, two pairs of genital markings located closely to male pores in xviii, and the presence of septum 8/9. The COI fragments are also provided for Metaphire giengensis sp. nov.